Superalloys 1996 (Eighth International Symposium) 1996
DOI: 10.7449/1996/superalloys_1996_119_127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Formation of Serrated Grain Boundaries in Nickel Base Superalloys

Abstract: The growth kinetics of particles producing serrations on grain boundaries were studied on Astroloy and an experimental low misfit alloy. The serrations developed after applying an isothermal heat treatment a few degrees below the solvus temperature of the y ' phase. In both materials, it was observed that arms which originated from dendritic particles pushed the grain boundaries on both sides and consequently produced serrations of a few microns in size (category A). In addition, in the alloy with low misfit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
2
12
1
Order By: Relevance
“…height) of the serration is determined by the extent of the dendritic growth. This is consistent with the findings made by Henry et al (1991) and Danflou et al (1996). The growth behaviour of the ␥ precipitates is found to be determined by the degree of supersaturation maintained in the matrix.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…height) of the serration is determined by the extent of the dendritic growth. This is consistent with the findings made by Henry et al (1991) and Danflou et al (1996). The growth behaviour of the ␥ precipitates is found to be determined by the degree of supersaturation maintained in the matrix.…”
Section: Discussionsupporting
confidence: 93%
“…Correspondingly there is also an increase in the GBCR with decreasing cooling rate as the grain boundaries become more convoluted. Previous authors have also reported the presence of grain boundary serrations and linked their resultant size to the cooling rate experienced (Danflou et al, 1992(Danflou et al, , 1996Henry et al, 1991). Detailed SEM and TEM analysis of the grain boundaries in this work shows that the grain boundary serrations develop as a result of impingement of the grain boundary by the grow- Fig.…”
Section: Grain Boundary Serrationmentioning
confidence: 84%
“…Additionally, Nolfi's model has been adapted for the case of a migrating reaction interface, where the solute transport is controlled by short-circuit-type grainboundary diffusion. [24] Cellular precipitation is also favored under conditions of high plastic deformation. [25] However, other researchers argue that cellular structures could simply be eutectic phases made possible through incipient melting due to the local segregation of solute atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] Reactions of such category generally result in the formation of multi-phase cellular structure. This type of phenomenon is of significance to the development of certain Ni-base superalloy grades, as the formation of cellular structures may be accompanied by the presence of detrimental topologically closed packed (TCP) phases.…”
Section: Introductionmentioning
confidence: 99%
“…al [16]. Heat treatments were tailored such that both microstructures had similar γ grain size distributions.…”
Section: Methodsmentioning
confidence: 99%